The Track‐by‐Day Method for Monitoring the Rodent Estrous Cycle. Issue 4 (11th April 2023) - Raimondi, Gianna M.; Tripp, Rebecca; Ostroff, Linnaea E.
Abstract: The exclusion of female subjects from preclinical neuroscience research has traditionally been justified in part by concerns about potential effects of cycling ovarian hormones on brain function. There is evidence that some behavioral and neurobiological measures do change over the estrous cycle and, as the use of female subjects becomes increasingly routine, there is a greater demand for accessible cycle‐tracking methods. Conventional estrous cycle staging requires expert training in the qualitative interpretation of vaginal cytology smears, which serves as a barrier for novice researchers. In addition, definitions and reporting practices are not standardized across laboratories, which makes it difficult to compare results across studies and likely contributes to a false perception of the cycle as ephemeral and inconsistent. Here, we describe a streamlined method for monitoring the estrous cycle in rats, which we term Track‐by‐Day. It is simple to implement and inherently produces consistent reporting. Our protocol should serve to demystify and facilitate adoption of cycle tracking for those new to the practice. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Collection and staining of vaginal smears Basic Protocol 2 : Track‐by‐Day classification of vaginal smears Support Protocol : Preparation of gelatin‐subbed slides